PENINGKATAN KEAKTIFAN DAN HASIL BELAJAR MELALUI MODEL PEMBELAJARAN PROBLEM BASED LEARNING MATERI INOVASI TEKNOLOGI BIOLOGI KELAS X A SMAN 6 MADIUN TAHUN PELAJARAN 2022/2023 - Laili Nailul Farich; Ima Agung Nurcahyo; Cicilia Novi Primiani (Universitas Lancang Kuning, 2023)
The purpose of this study was to increase the activity and learning outcomes of students in biology learning material for biological technology innovation in class XA SMAN 6 Madiun by applying the Problem Based Learning learning model.This research is a class action research (CAR) with the Kemmis & Taggart model which was carried out in two cycles. The data collected was in the form of data on students' active learning and cognitive learning outcomes, namely the pre-test and post-test scores of cycles I and II. Data on students' learning activeness was taken by observation and analyzed descriptively by describing the percentage of each aspect in learning activeness. Cognitive learning outcomes data were taken by pre-test and post-test cycle I-cycle II and tabulated in the form of class averages. The increase in students' cognitive learning outcomes can be seen from the difference between the mean value of the second cycle post-test and the first cycle post-test average value. The results showed that the application of the Problem Based Learning (PBL) learning model in biology subject material Biological Technology Innovation could increase the activity and cognitive learning outcomes of class X A students of SMAN 6 Madiun. Increasing the activeness of learning students can be seen from each aspect of activeness.